An investigation into the variability of ABS 3D printing filaments due to differing dye colourants used by manufacturers - Wright, Gary (Cranfield University, 2019)
Despite advances in polymer filaments available for 3D printing, ABS remains an attractive polymer for use because of its versatility, good mechanical properties and cost effectiveness. Personal experience has highlighted variability between manufacturer’s ranges and even occasionally between the colours within those ranges. This variability seems to affect the quality of print and level of success achieved. In this study, analytical techniques, including X-ray diffraction (XRD), Dynamic Mechanical Analysis (DMA), Differential Scanning Calorimetry (DSC), RAMAN spectroscopy, and Fourier Transform Infra-Red (FTIR) spectroscopy, as well as mechanical tensile testing and Scanning Electron Microscopy (SEM) imaging, were used to compare and contrast selected colours from 3 different manufacturer’s ranges. This allowed comparison by chemical composition, physical properties such as glass transition temperature and by mechanical performance. Differences were found in their chemical composition, base polymer properties and their mechanical performance and some of this data did not match the information supplied by the manufacturers. A large analytical comparative study such as this lends itself to becoming quite complex, and this was reinforced by the practical difficulties encountered during the work which limited the conclusions that could be drawn. Significant variability was found between the manufacturer’s ranges themselves, and in some instances by colours within ranges. These differences were evident by way of DSC and DMA responses for glass transitions, compositions shown by FTIR and crystallinity from XRD, and occasionally also large statistically significant variability in mechanical tensile properties. Despite these findings, and practical experience implying otherwise, there was no conclusive link found that the variability of colour of the filament is responsible for the variability of print quality. Indeed, the variability between the base polymer i blends comparing each of the manufacturer’s ranges was found to be higher than that between the colours within the ranges themselves.